THE ROLE OF TEACHERS AS AGENTS OF TRANSFORMATION IN PAI LEARNING INNOVATION IN THE DIGITAL ERA - Wahidah, Nur; Agus Puspita W, Dhevin M.Q (International Conference on Humanity Education and Society (ICHES), 2025)
The role of teachers as transformation agents is very important in Islamic Religious Education (PAI) learning innovation in the digital era. Challenges such as low digital literacy and limited technological infrastructure require a strategic approach in integrating learning technology. This research aims to identify the role of PAI teachers in developing digital learning innovations, the challenges they face, and the opportunities available. This research uses a descriptive qualitative approach withdata collection techniques in the form of in-depth interviews, observation and documentation. The informants consisted of PAI teachers in middle and high schools in Jember Regency. The research results show that PAI teachers have utilized technology such as LMS, interactive applications, and blended learning models to create relevant and interesting learning. The main challenges include a lack of digital literacy training and limited infrastructure, but opportunities such as government training programs are a strategic solution. This research concludes that technology integration can increase students' understanding of religious values while forming an Islamic character that is adaptive to the digital era.